Imam Bayhaqi's interpretation in al-Sunan al-Kubra: collection documentation and studying / Imad Abdul Jabbar Khalaf - Imad Abdul Jabbar, Khalaf (2016)
This research has dealt with the collection of the explanatory narrations of Emama AlBayhaqi in the Major Sunan, and the tha documentation, study and comment on them, and the importance of this study dwell in: collecting the explanatory Book according to the order of Holy Quran. From Al-fatihah to Al- NAss, it contains a lot of explanatory and right narrations. Which was reckond on by many explainers..After the era of Al- Emam, the knowledge of the explanatory creation of Al- Emam Al-Bayaki, which was clarified in his comments and tipping through his classification. The aims of the research: to concentrate on the maxim because it is the origin of the explanation for Al- Emam Al-Bayhaqi May Allah forgive him added conative approach to the statement of Al-Emama Al-Bayhaqi, the truth and statement of the narrations in the book od Major Sunan. Researcher Methodology and procedures: The nature of the research which is based on the study of narration’s subject in the book of MajorSunan, and the collection of explanatory narrations and what is related to it from Emma’s comments, and then the investigation of its veracity, Through the totalitarian reading of the Book of Major Sunan, in addition to the descriptive and analytical approach according the extracted teats from the book Major Sunan and their analysis. The scholar had gothered all these narration of also, he detected all the traditions and he registerd for all the rules of the scholars and critized them from the correction or weakness. he made a single section for each subject because he wanted to benefit all the readers who read the life story Emam Bayhaki and the writing of the Major Sunan, in which he insisted to give more benefits, and that was through a systematic reading it also follows other translations and Sheikhs. This section included, the era of Al-Bayhaki from the side of politics, society, science, biography, growing up, the trips to look for more knowledge, sheikhs, students, scientific status, the appreciation of scientists, and the scientific effects, In addition to the importance of the Book of Greatest Sunan and methodology of Al-Bayhaki through the explanatory narrations. The second section included the distribution of the narration according to the Holly Quran from Al-Fatihah till Al-Nass. With the appropriate comments, a reportage study, in addition to a small part about classes of some explainers during his era, this explained the superiority of Nishapur scientists, During that period, and to conclude the researcher with the outputs. Which is achieved from the researchers? Where that book took a lot of efforts from Al- Bahaki’s life – May Allah forgive him it was finished after twenty seven years. Emam AlBayhaqi has considered it as his aim and followed doctrine. He made the translations of sections extracted from the speeches, even if it is the lowest one, and he formulates it through his weight to ensure the truth of his ideas. In this book "The Greatest Sunan" there are about 700 narrations for E-mam Al-Bayhaqi, they were exacted from Sunan as follow: Sahih Bukhari Book (193) narrations. Al Trarmidhi Sunan (26) narrations. Musnad Emam Ahmed (54) narrations. Sunan Abu Daoud (87) narrations.Mustadrak Al Hakim (88) narrations. The mother ’s book (60) narrations . That means the total number is (630) narrations. (450) narrations of them are about reasons of the decent. However, the number of the weak narrations are about (30) narrations.The rest of narrations were kept by Emam Al-Bayhaki himself,or they are found in the explanatory Books. But I didn’t find in the Book of the Greatest Sunan “ narrations for the following 13 Sourah. Sabaa. A-Zukhruf, Al-Rahman, Al-Mulk, Al- Naziaat, Al – Infitar, Al –Tarek, Al – Shams, Al – Adiat, Al- Kariah, A- Assar, Al Homzah, Al- Feel.However, I have found them in the other books of Al-Emama And Allah Grants Success.